Analisa Pengaruh Jumlah Muatan Terhadap Beban Sloshing Tangki Pada Kapal Tanker Dengan Metode Numerik - Amar Ma'ruf; Daeng Paroka; Habibi Palippui (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Tank is a cargo storage container and is the main part of ships carrying liquids and gases so that the cargo is maintained and safe. As a storage medium, the tank will always get loads that come from inside as well as loads that come from outside the tank, sloshing is one of the loads that come from inside. Sloshing occurs due to the movement of the vessel/tank resulting in free motion of oscillating fluid hitting the tank wall. The purpose of this study was to find the effect of the load on the movement and sloshing load on the tank with variations in the amount of load. The tank model used is a reference to a general purpose tanker transporting crude oil in two-dimensional rectangular conditions (midship) with a width of 8,6 m and a height of 8 m on both the left and right sides. The variations used are 10% load volume (0,8 m high), 30% volume (2,4 m high), 50% volume (4 m high), 70% variation (5,6 m high) and 90% variation (high 7,8 m). The simulation was carried out with a numerical method, namely Computational Fluid Dynamic (CFD) using Ansys Fluent software. The back of the tank is based on the movement of the ship which in this case is limited to heaving and rolling motion, from the simulation results it is concluded that the biggest sloshing effect occurs at the load volume variation of 10%, the frequency is 2.145, while the greatest pressure occurs at the lower left corner of the tank with a pressure of 443,29 Kpa.